Case Report: Concurrent neurofibromatosis type 1 with papillary thyroid carcinoma and gastrointestinal stromal tumor - Dweik, Ruba; Faroun, Jana; Yacoub, Rita; Smerat, Mohammad I.; Abu Asbeh, Yousef (Frontiers in Oncology, 2025)
Neurofibromatosis type 1 (NF1) is a genetic disorder characterized by benign tumors such as neurofibromas and café-au-lait spots, with affected individuals at increased risk for malignant tumors, including gastrointestinal stromal tumors (GIST) and, rarely, papillary thyroid carcinoma (PTC). This case report presents a 30-year-old Palestinian woman with NF1 who experienced severe abdominal pain and melena, leading to the diagnosis of a jejunal GIST, which was surgically removed. Postoperative imaging revealed cervical and thoracic lesions. A follow-up PET scan indicated hypermetabolic masses in the thyroid and chest. Subsequent surgery confirmed the diagnosis of PTC and neurofibromas, with whole exome sequencing identifying a likely pathogenic variant in the NF1 gene. This case demonstrates the value of comprehensive evaluation and genetic counseling for NF1 patients due to the risk of multiple tumors, which points to careful monitoring for early detection and management. To our knowledge, this instance is the first reported case of concurrent GIST and PTC in a patient with NF1.